Description of Sugar Intake and Academic Performance Among Adolescents at SMPN 28 Bandung - Ema Arum Rukmasari; Kharissa Permata Junita; Dyah Setiorini (International Journal of Science and Society, 2025)
Academic achievement is influenced by multiple factors, including daily nutritional intake. Sugar consumption is often associated with cognitive function and concentration; however, empirical findings remain inconsistent. This study aimed to analyze the relationship between sugar intake and academic achievement among adolescents. A quantitative study with a correlational design was conducted at SMPN 28 Bandung involving 164 students selected through simple random sampling. Sugar intake data were collected using a Semi-quantitative Food Frequency Questionnaire (SFFQ) and analyzed using the NutriSurvey program, while academic achievement was obtained from students’ report card scores across five semesters. The collected data were analyzed using Pearson’s correlation test because both variables were measured on a ratio scale and met the normality assumption. The results showed that the mean academic achievement score was 90.92 ± 2.34 and the mean sugar intake was 103.01 ± 58.32. Pearson correlation analysis indicated no significant relationship between sugar intake and academic achievement (r = -0.026; p = 0.737). The correlation strength was very weak and negative in direction. It can be concluded that sugar intake was not significantly associated with academic achievement among the study respondents. Other factors beyond sugar intake are likely to play a greater role in determining academic performance.